Communication Patterns Between Sangihe and Bugis Ethnics in Galala Village - Putri Nurdiana Jailan; Iksan Hasim (Peneliti.net, 2021)
Communication is a process where the interaction between communicators and communicants who exchange messages in it that occurs directly or indirectly, communication itself can be said to be the most crucial thing in this life. Inter-ethnic communication patterns Sangihe and ethnic Bugis are interesting to study further, because the two ethnic groups have different cultural backgrounds. The communication pattern is a model of the communication process that relies on morals and values ​​prevailing in society. So that with the communication model and part of the communication process it will be possible to find a pattern that is suitable and easy to use in communicating in accordance with morals in communicating. Qualitative research is research that uses open interviews to examine and understand individual attitudes, views, feelings, and behaviors. or a group of people. Qualitative research must also understand the attitudes, views, feelings, and behaviors of both individuals and groups of people. This is done face-to-face and communication using communication media.